Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.